"Economic Migrants" or "Middling Transnationals"? East European Migrants' Experiences of Work in the UK. (17th March 2011) - Parutis, Violetta
Abstract This article is devoted to the exploration of Polish and Lithuanian migrants' work experiences in the United Kingdom. It argues that it is hard to categorize these individuals as highly skilled or low‐skilled because, in spite of their relatively high qualifications, they often occupy low‐skilled positions in the United Kingdom. Therefore, the article suggests that these migrants are "middling transnationals" (Conradson and Latham, 2005a). Although they are classified as economic migrants, many of them have migrated to the United Kingdom not only in order to earn money but also to try life abroad, see the world, or learn English. Following Bourdieu's terminology, the article suggests ways in which migrants use different cultural capital (skills, qualifications, social environment) to enhance their economic capital in the United Kingdom, but also ways in which these different forms of migrants' capital are interrelated. The findings suggest that Eastern Europeans are highly mobile in the British labour market. Provided they possess necessary linguistic skills, migrants progress from "any job" to a "better job" in search of a "dream job". The article emphasises that this transition in the British labour market became easier after Poles and Lithuanians became EU citizens, whereby they were granted the right to work and improved access to education services in the United Kingdom. The article also argues that viewing migrants' work experiences in the context of their future plans helps to understand better why working below qualifications is acceptable to many East Europeans in the United Kingdom. This is either because it helps them maximise their income and return to their home country as soon as possible, or because a low‐skilled position helps them to improve other skills (e.g., English) and serves as a stepping stone to better career opportunities in the future.